Tourism in coastal areas. Local development initiative with small businesses - García Saltos, María Beatriz; Domínguez Junco, Osvaldo; Labrador Afre, Marigreysi (Revista Universidad de Guayaquil, 2017)
The coastal zones are interesting sites, because they contain all kinds of resources that are of interest to tourism. Biotic and abiotic components are intertwined in unique ecosystems, that provide abundant biological diversity, with environments, marine and terrestrial in turn, refuges of typical flora and fauna, with species of passerby birds, combined with the attractive space of sun and beach, the abundant breeze with a peculiar aroma, the coming and going of fishermen and merchants, whose idiosyncrasy differs from the environment of a city and rural area or intramontane, providing a rich cultural value that attracts the visitor. This investigation offered variants that allow the promotion of tourism for local development in these places, especially small communities, since at times, their own inhabitants are unaware of the treasure they have. In order to do this, it was involved in matters related to tourism and its most demanding needs today, as well as the values that treasure those areas and that constitute an unparalleled attraction. The creation of small, environmentally friendly tourist businesses can be a driving force for local development. Historical methods of documentary research were applied, as well as empirical ones based on the observation and surveys, through simple random sampling in two coastal communities, one Cuban and one Ecuadorian, offering general ideas applicable to any coastal zone, especially, those of the tropics and subtropics of the planet and very punctually, in those that count on wonderful ecosystems like mangroves.